Novel octahedral tilt system a + b + c + in (1 − x)Na0.5Bi0.5TiO3–xCdTiO3 solid solutions - Ignatans, R.; Dunce, Marija; Birks, Ēriks; Šternbergs, Andris (Springer Verlag, 2017)
(1 − x)Na0.5Bi0.5TiO3–xCdTiO3 solid solutions in the whole concentration range (0.0 ≤ x ≤ 1.0) were studied by means of X-ray diffraction, dielectric spectroscopy and polarization measurements. The study was mainly focused on crystalline structure of the compositions, depending on their place in the phase diagram. The solid solution system exhibits at least four different phases at room temperature, giving rise to paraelectric, ferroelectric and relaxor ferroelectric behaviour. There were proposed appropriate space groups for each of these phases, using Rietveld refinement method for analysis of the X-ray diffraction patterns and taking into account polarization measurement results. Unexpected and unusual octahedral tilt systems—a + a + a + and a + b + c +—were found in certain CdTiO3 concentration ranges. The tilt system a + b + c +, which was detected in the ferroelectric phase, was evidenced for the first time, as it has been theoretically predicted, but never experimentally observed before in any material. It was shown that ferroelectricity in (1 − x)Na0.5Bi0.5TiO3–xCdTiO3 solid solutions arises not only from the Ti+4 displacements, but also from the polar distortions in square planar and cubooctahedral cation A-sites. Upon heating, at a phase transition from the ferroelectric to the paraelectric state, a + b + c + tilt system transforms into a + a + a +. The studied compositions were compared with (1 − x)Na0.5Bi0.5TiO3–xCaTiO3 solid solution system, as CdTiO3 and CaTiO3 are crystallographically very similar. It was revealed that both constituents behave very differently. CaTiO3 in (1 − x)Na0.5Bi0.5TiO3–xCaTiO3, even in low concentrations, stabilizes solid solutions in its Pnma space group, unlike its counterpart CdTiO3 in the studied materials.
This work has been supported by National Research Program in the framework of project “Multifunctional Materials and composites, photonics and nanotechnology (IMIS2)”.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; structure; NBT; ferroelectrics; x-ray diffraction; tilt system; solid solution